Bamboo Plantation in Dhalbhum Tract of Singhbhum District of Bihar - Prasad, B. N. (Indian Forester, 1965)
Dhalbhum tract in contrast to the other portions of Singhbhum district of Chotanagpur is characterized by plane configuration of land, and red soil. Extensive waste lands are available in and outside forest demarcation. Bamboo plantation in smaller scale was tried in the fourties with very good result. With the evolution of the technique of raising large scale bamboo plantation with seeds, a target of 11,882 acres has heen kept for plantation in this tract in the 3rd Five-Year Plan. The article describes the salient features, technique and various problems of the first large scale bamboo plantation. It may be of some help in organising large scale bamboo plantation in other States.